Implementation of Wordwall-Based Game-Based Learning to Enhance Instructional Design Creativity of PIAUD Students - Deti Tri Kurnia; Alisyah Rahmadani; Tiara Devani Hasibuan; Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the implementation of Wordwall-based game-based learning in enhancing the instructional design creativity of Early Childhood Islamic Education (PIAUD) students. The research employed a quantitative approach with a quasi-experimental design. The subjects of this study were PIAUD students enrolled in instructional media development courses. Data were collected through observation, questionnaires, and documentation, while statistical analysis was used to examine differences before and after treatment. The results indicate that the use of Wordwall in game-based learning significantly improves students’ creativity in designing innovative, interactive, and engaging instructional materials. Furthermore, students demonstrated enhanced reflective abilities and greater exploration of creative ideas during the learning process. Therefore, the implementation of Wordwall-based game-based learning is effective as a learning strategy to improve the quality of instructional design among PIAUD students.